Rapid Identification of Antioxidant Compounds of Genista saharae Coss. & Dur. by Combination of DPPH Scavenging Assay and HPTLC-MS - Djamila Meriane; Grégory Genta-Jouve; Mohamed Kaabeche; Sylvie Michel; Sabrina Boutefnouchet (Molecules, 2014)
Genista species are sources of antioxidant phenolic compounds such as O- and C-glycosylﬂavonoids and isoflavonoids. A combination of a DPPH scavenging assay with HPTLC-MS, a fast and efficient method for identification of bioactive compounds, has been applied for evaluation of the radical scavenging activity of metabolites from Genista saharae Coss. & Dur. Different organs collected at various periods have been compared. Identification of antioxidant compounds was obtained by elution of the major DPPH-inhibition zones. The resulting HPTLC-MS analysis under moderately polar conditions, coupled to the DPPH results led to the putative identification of two antioxidant isoflavone aglycones: 3',4',5,7-tetrahydroxyisoflavone (1) and ficuisoflavone (3), whereas polar migration conditions led to the identification of the glycosides 5-methoxy-4',7-trihydroxy-8-glucopyranosylisoflavone (4) and 4',5-dihydroxy-7-methoxyisoflavone-4'-O-β-D-gluco-pyranoside (5). Evaluation of percentage of inhibition of DPPH radical by the purified isoflavone 4 from the root extract showed that it affords a moderate contribution to the total radical scavenging activity of the extract.